Novel role of immature myeloid cells in formation of new lymphatic vessels associated with inflammation and tumors. Issue 2 (13th April 2017) - Ran, Sophia; Wilber, Andrew
Abstract : Review on lymphatic endothelial progenitors, primarily of myeloid origin, which induce new lymphatic vessels in inflamed tissues and tumors. Abstract: Inflammation triggers an immune cell-driven program committed to restoring homeostasis to injured tissue. Central to this process is vasculature restoration, which includes both blood and lymphatic networks. Generation of new vessels or remodeling of existing vessels are also important steps in metastasis—the major cause of death for cancer patients. Although roles of the lymphatic system in regulation of inflammation and cancer metastasis are firmly established, the mechanisms underlying the formation of new lymphatic vessels remain a subject of debate. Until recently, generation of new lymphatics in adults was thought to occur exclusively through sprouting of existing vessels without help from recruited progenitors. However, emerging findings from clinical and experimental studies show that lymphoendothelial progenitors, particularly those derived from immature myeloid cells, play an important role in this process. This review summarizes current evidence for the existence and significant roles of myeloid-derived lymphatic endothelial cell progenitors (M-LECPs) in generation of new lymphatics. We describe specific markers of M-LECPs and discuss their biologic behavior in culture and in vivo, as well as currently known molecular mechanisms of myeloid-lymphatic transition (MLT). We also discuss the implications of M-LECPs for promoting adaptive immunity, as well as cancer metastasis. We conclude that improved mechanistic understanding of M-LECP differentiation and its role in adult lymphangiogenesis may lead to new therapeutic approaches for correcting lymphatic insufficiency or excessive formation of lymphatic vessels in human disorders.